STUDI TENTANG SULAMAN BAYANGAN KAGASA DI NAGARI BARUNG-BARUNG BALANTAI KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - EZRIANI, Dr. Budiwirman, M.Pd, Drs. M. Nasrul Kamal, M.Sn (Serupa The Journal of Art Education, 2014)
This research is to describe the tecknik, motif and the right places of motifSulaman Bayangan Kagasa. As for the use of this research to describe the quantity and the quality of research which involved the teoritis and practice.This research use descriptive qualitative method. The instrument used isdescriptive qualitative analysis. The subject of this research in Sulaman Bayangan Kagasa.Based of the result of this research it can concludes that: (a) The tecknik of Sulaman Bayangan Kagasa is decorative tecknik. (b) The motif of Sulaman Bayangan Kagasa is flora and fauna natural decorative and geometris. (c) The right places of Sulaman Bayangan Kagasa ara triangle pattern, regtangle pattern, perimeter pattern. For the next researcher he can develop the descriptive qualitative method in research to know the perception of Sulaman Bayangan Kagasa crafters.Kata kunci: Studi, sulaman bayangan kagasa.